Effects of a single short exposure to blue light on cognitive performance - Tonetti, L.; Natale, V. (Chronobiology International, 2019)
The aim of the present study is to explore the effects of a single short one-minute exposure to blue light on cognitive performance. For this purpose, 32 young adults (16 females, mean age 24.06 ± 1.88 years) took part in a within-subjects research design, under two conditions: blue light and no light. Under both conditions, they performed the lexical decision task (LDT) in order to assess the degree of automatic activation of semantic memory through an embedded semantic priming (reaction times to prime - reaction times to target), together with the Attention Network Test (ANT) to assess the efficiency of the alerting, executive and orienting networks. During the LDT, a significantly stronger semantic priming under the blue light condition compared to no light was observed, while during the ANT a significant difference in orienting network efficiency between conditions was observed. The present data appear to highlight that even a single short exposure to blue light has an effect on cognitive performance in young adults.